Capacity building in environmental and occupational health in Sri Lanka1. Issue 1 (27th December 2011) - Wickremasinghe, Ananda R.; Peiris‐John, Roshini; Nandasena, Sumal; Delzell, Elizabeth; Tipre, Meghan; Sathiakumar, Nalini; Claudio, Luz; Robins, Thomas
Abstract Background Although environmental and occupational health (EOH) research and services in Sri Lanka have a long history, policies related to EOH are outdated. Methods We review the International Training and Research in Environmental and Occupational Health (ITREOH) program in Sri Lanka that commenced in 2006 as a collaboration between the University of Alabama at Birmingham and the Faculty of Medicine of the University of Kelaniya, Sri Lanka. Results The program has trained over 20 scientists in conducting EOH research. New pioneering research in EOH was initiated. The program was instrumental in furthering the training and research in EOH by initiating a MPH degree program, the first in the country. Conclusions The program has established North–South, South–South and in‐country collaborations between institutions and scientists, increasing the visibility of EOH in the future. Am. J. Ind. Med. 56:1–10, 2013. © 2011 Wiley Periodicals, Inc.